Students’ Perception on Webtoon Application as a Reading Medium for Vocabulary Enhancement - Aulia, Dita; Ulfa, Siti Maria (Universitas Islam Negeri Raden Intan Lampung, 2025)
Reading skills and vocabulary mastery are crucial aspects in language learning. In recent years, digital media such as Webtoon have become a popular alternative to improve reading comprehension and enrich students' vocabulary. Although the use of Webtoon is increasingly widespread, research examining its effectiveness as a learning medium is still relatively limited. Therefore, this study aims to analyze students' perceptions of the Webtoon application as a means of reading to improve their vocabulary. The method used in this study was a qualitative approach, involving interviews with teachers and students of grade VIII MTs An Nasuriyah. The results of the study revealed that Webtoon succeeded in increasing students' interest in reading. The combination of visual and text elements in Webtoon helps students understand new words in a clearer context, making it easier for them to remember vocabulary. However, there are several challenges faced, such as the gap in access to digital devices and the tendency of students to focus more on images than text. Teachers recognize the potential of Webtoon as a learning medium, but emphasize the need for guidance so that the use of this media is more focused and effective. Overall, this study concludes that Webtoon can function as an effective tool in vocabulary learning, especially when combined with conventional learning methods. Therefore, it is recommended to conduct further research to explore optimal strategies in utilizing digital comics in language learning and find solutions to overcome obstacles to technology access, so that the benefits can be felt by all students.